Mass spectrometric assays monitoring the deubiquitinase activity of the SARS-CoV-2 papain-like protease inform on the basis of substrate selectivity and have utility for substrate identification - Brewitz, L; Chan, HTH; Lukacik, P; Strain-Damerell, C; Walsh, MA; Duarte, F; Schofield, CJ (Elsevier, 2023)
The SARS-CoV-2 papain-like protease (PLpro) and main protease (Mpro) are nucleophilic cysteine enzymes that catalyze hydrolysis of the viral polyproteins pp1a/1ab. By contrast with Mpro, PLpro is also a deubiquitinase (DUB) that accepts post-translationally modified human proteins as substrates. Here we report studies on the DUB activity of PLpro using synthetic Nε-lysine-branched oligopeptides as substrates that mimic post-translational protein modifications by ubiquitin (Ub) or Ub-like modifiers (UBLs), such as interferon stimulated gene 15 (ISG15). Mass spectrometry (MS)-based assays confirm the DUB activity of isolated recombinant PLpro. They reveal that the sequence of both the peptide fragment derived from the post-translationally modified protein and that derived from the UBL affects PLpro catalysis; the nature of substrate binding in the S sites appears to be more important for catalytic efficiency than binding in the S′ sites. Importantly, the results reflect the reported cellular substrate selectivity of PLpro, i.e. human proteins conjugated to ISG15 are better substrates than those conjugated to Ub or other UBLs. The combined experimental and modelling results imply that PLpro catalysis is affected not only by the identity of the substrate residues binding in the S and S′ sites, but also by the substrate fold and the conformational dynamics of the blocking loop 2 of the PLpro:substrate complex. Nε-Lysine-branched oligopeptides thus have potential to help the identification of PLpro substrates. More generally, the results imply that MS-based assays with Nε-lysine-branched oligopeptides have potential to monitor catalysis by human DUBs and hence to inform on their substrate preferences.